Antigenic diversity in Theileria parva populations from sympatric cattle and African buffalo analyzed using long read sequencing - Allan, F.K.; Jayaraman, S.; Paxton, E.; Sindoya, E.; Kibona, T.; Fyumagwa, R.; Mramba, F.; Torr, S.J.; Hemmink, Johanneke D.; Toye, Philip G.; Lembo, T.; Handel, Ian G.; et al. (Frontiers Media, 2021)
East Coast fever (ECF) in cattle is caused by the Apicomplexan protozoan parasite Theileria parva, transmitted by the three-host tick Rhipicephalus appendiculatus. The African buffalo (Syncerus caffer) is the natural host for T. parva but does not suffer disease, whereas ECF is often fatal in cattle. The genetic relationship between T. parva populations circulating in cattle and buffalo is poorly understood, and has not been studied in sympatric buffalo and cattle. This study aimed to determine the genetic diversity of T. parva populations in cattle and buffalo, in an area where livestock co-exist with buffalo adjacent to the Serengeti National Park, Tanzania. Three T. parva antigens (Tp1, Tp4, and Tp16), known to be recognized by CD8+ and CD4+ T cells in immunized cattle, were used to characterize genetic diversity of T. parva in cattle (n = 126) and buffalo samples (n = 22). Long read (PacBio) sequencing was used to generate full or near-full length allelic sequences. Patterns of diversity were similar across all three antigens, with allelic diversity being significantly greater in buffalo-derived parasites compared to cattle-derived (e.g., for Tp1 median cattle allele count was 9, and 81.5 for buffalo), with very few alleles shared between species (8 of 651 alleles were shared for Tp1). Most alleles were unique to buffalo with a smaller proportion unique to cattle (412 buffalo unique vs. 231 cattle-unique for Tp1). There were indications of population substructuring, with one allelic cluster of Tp1 representing alleles found in both cattle and buffalo (including the TpM reference genome allele), and another containing predominantly only alleles deriving from buffalo. These data illustrate the complex interplay between T. parva populations in buffalo and cattle, revealing the significant genetic diversity in the buffalo T. parva population, the limited sharing of parasite genotypes between the host species, and highlight that a subpopulation of T. parva is maintained by transmission within cattle. The data indicate that fuller understanding of buffalo T. parva population dynamics is needed, as only a comprehensive appreciation of the population genetics of T. parva populations will enable assessment of buffalo-derived infection risk in cattle, and how this may impact upon control measures such as vaccination.